Structural elements in the complex character of the nationbuilding process in Perú - Pacheco Romero, Luis (2009)
What we have in Peru at the beginning of the XXIst century is a formal and not a real nationState. It did not let the market to perform efficiently; neither did it properly satisfy the demands of the majority of the people. This led to the State’s loss of legitimacy. This can be explained by the lack of a political elite capable of putting forward a long-term project to the country. The reversal of that deficit works on the premise that the historical project will contribute decisively in the nation-building process only if it accomplishes to carrying out the essential interests of the population and to safeguard the strategic interests of the country.